Comprehensive Analysis of Cytomegalovirus pp65 Antigen-Specific CD8+ T Cell Responses According to Human Leukocyte Antigen Class I Allotypes and Intraindividual Dominance - Hyun, Seung-Joo; Sohn, Hyun-Jung; Lee, Hyun-Joo; Lee, Seon-Duk; Kim, Sueon; Sohn, Dae-Hee; Hong, Cheol-Hwa; Choi, Haeyoun; Cho, Hyun-Il; Kim, Tai-Gyu (Frontiers in Immunology, 2017)
To define whether individual HLA class I allotypes are used preferentially in human CMV-specific CTL responses, CD8+ T cell responses restricted by up to six HLA class I allotypes in an individual were measured in parallel using K562-based artificial antigen-presenting cells expressing both CMV pp65 antigen and one of 32 HLA class I allotypes (7 HLA-A, 14 HLA-B, and 11 HLA-C) present in 50 healthy Korean donors. The CD8+ T cell responses to pp65 in the HLA-C allotypes were lower than responses to those in HLA-A and -B allotypes and there was no difference between the HLA-A and HLA-B loci. HLA-A*02:01, -B*07:02, and -C*08:01 showed the highest magnitude and frequency of immune responses to pp65 at each HLA class I locus. However, HLA-A*02:07, -B*59:01, -B*58:01, -B*15:11, -C*03:02, and -C*02:02 did not show any immune responses. Although each individual has up to six different HLA allotypes, 46% of the donors showed one allotype, 24% showed two allotypes, and 2% showed three allotypes that responded to pp65. Interestingly, the frequencies of HLA-A alleles were significantly correlated with the positivity of specific allotypes. Our results demonstrate that specific HLA class I allotypes are preferentially used in the CD8+ T cell immune response to pp65 and that a hierarchy among HLA class I allotypes is present in an individual.